วงจรกรองผ่านแถบแบนด์กว้างไมโครสตริปที่มีความคมความถี่ตัดสูงและ จำกัดความถี่ปลอมเทียมแบนด์กว้าง Wideband Microstrip Bandpass Filters with High Selectivity and Wide Suppressed Spurious - วามะกัน, วุฒินันท์; อ่อนน้อม, สุรินทร์; วางขุนทด, สมสิน (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2015)
บทคัดย่อ บทความนี้นำเสนอวงจรกรองผ่านแถบกว้างโหมดคู่ โดยใช้เรโซเนเตอร์วงแหวนสี่เหลี่ยมที่มีการปรับจูนความกว้างแถบผ่านด้วยสตับคู่ซึ่งสร้างสองโหมด โดยใช้ตัวรบกวนแบบใหม่ด้วยการเจาะร่องเป็นรูปสี่เหลี่ยมผืนผ้าพับเป็นลูปซํ้าที่หลังตัวป้อนอินพุตและตัวป้อนเอาต์พุต และลดขนาดของเรโซเนเตอร์ด้วยวิธีการใส่สตับปลายเปิดอิมพีแดนซ์ตํ่าที่กึ่งกลางภายในด้านทั้งสี่ของวงแหวนสี่เหลี่ยม ส่งผลให้เกิดค่าการสูญเสียจากการใส่แทรกประมาณ 0.35dB ที่ความถี่กลาง 4.125 GHz และค่าสูญเสียย้อนกลับตํ่ากว่า10 dB ตลอดแถบความถี่ 3.13 GHz ถึง 5.2 GHz ซึ่งสามารถเพิ่มค่าความคมของความถี่ตัดและ เพิ่มความสามารถการจำกัดความถี่ปลอมเทียมนอกช่วงผ่านแถบ ด้วยการนำเอาวงจรเรโซเนเตอร์สองตัวมาต่อคาสเคดกันแบบอินเตอร์ดิจิทัล ส่งผลให้เกิดค่าความคมความถี่ตัดสูงกว่า 360dB/GHz ค่าความถี่ปลอมเทียมนอกแถบผ่านตํ่ากว่า 15 dB ได้ถึง 18 GHz และขนาดของเรโซเนเตอร์ต้นแบบลดลงประมาณ 48% Abstract This paper presents a dual-mode wideband bandpass filter based on the square ring resonator with two tuning stubs used to control pass band. The degenerate dual mode with a novel perturbation utilizes meander loop perturbation rectangular slots at the input and output ports in which is able to reduce the size resonator. Then is put the open-stubs with low impedance at the middle within the four sides of the square ring resonator. As a result, the value of an insertion loss is 0. 35 dB and return loss less than 10 dB at 3.13 GHz to 5.2 GHz frequency band. The proposed work can be increase high selectivity signal and improved the circuit to limited spurious frequencies outside the pass-band with two resonator interdigital Cascade. As a result, the value of high selectivity signal greater than 360 dB/GHz and spurious frequencies out side the pass band of less than 15 dB up to 18 GHz. The size of prototype has the reduction about 48%